2018
DOI: 10.12680/balneo.2018.227
|View full text |Cite
|
Sign up to set email alerts
|

The study on the importance of effects after the ultrasound use in the recovery of patients with lower lumbar discopathy

Abstract: The low back pain is a public health problem, affecting the adult population and the young one. It is estimated that 90% of the population will experience at least one episode of lower lumbar pain during their lifetime, half of whom may have a second painful episode during the same year. Frequently, the mechanical cause (the pain is somatic and deep, caused by lesions in the musculoskeletal tendon or ligament, in non-specific degenerative or inflammatory diseases) but also the psychosocial factors are incrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…One of the analgesic procedures for electrotherapy is TENS, which can be an alternative to NSAIDs, which have side effects. Studies showed a reduction in pain and a decrease in the amount of NSAIDs used [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…One of the analgesic procedures for electrotherapy is TENS, which can be an alternative to NSAIDs, which have side effects. Studies showed a reduction in pain and a decrease in the amount of NSAIDs used [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…The rhythmic alternation of inhibitory/exciting effects is, therefore, achieved with the following consequences: the activation of cellular functions, hyperemia at the level of the deep vessels, the performing of a deep micro-massage for the striated muscles. Ultrasounds (54) were used for biological effects, that is: the increase of cell membrane permeability, molecular activation by increasing the energetic level of the external atomic electrons, by increasing the respiratory activity at the cellular level and the activation of oxidative processes. The pursued physiological effects were those of pain relief, hyperemia and muscle relaxation.…”
Section: Materials and Methodmentioning
confidence: 99%
“…Due to the demographic changes, the aging of the population, it is expected that the prevalence of this disease will increase in the coming years. The non-pharmacological treatment includes, besides the elements of education of the person, (losing weight, avoiding prolonged standing, walking on the ground with elevations, weight lifting) physical exercise and the use of electrotherapy (54,55). The electrotherapy procedures frequently used involve ultrasound with pain-relief effect and muscle relaxation (56).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the recovery program in osteoarthritis includes a physical exercise program for increasing the muscle strength and endurance, increasing the joint mobility, maintaining muscle tone, as well as occupational therapy (34, 35). In the recovery program, electrotherapy (36) is recommended by applying low and medium frequency currents and ultrasound (37,38,39). Taking into account the adverse effects at the cardiovascular and digestive level, NSAIDs represent the second step in the management of osteoarthritis, being useful for the improvement of the symptoms, but the guides recommend them on the short term (ACR, 2008), (26,40,41).…”
Section: Introductionmentioning
confidence: 99%